Beginning Java game development with LibGDX - Stemkoski, Lee (Expert's voice in Java., 2015)
Design and create video games using Java, with the LibGDX software library. By reading Beginning Java Game Development with LibGDX, you will learn how to design video game programs and how to build them in Java. You will be able to create your own 2D games, using various hardware for input (keyboard/mouse, gamepad controllers, or touchscreen), and create executable versions of your games. The LibGDX library facilitates the game development process by providing pre-built functionality for common tasks. It is a free, open source library that includes full cross-platform compatibility, so programs written using this library can be compiled to run on desktop computers (Windows/MacOS), web browsers, and smartphones/tablets (both Android and iOS). Beginning Java Game Development with LibGDX teaches by example with many game case study projects that you will build throughout the book. This ensures that you will see all of the APIs that are encountered in the book in action and learn to incorporate them into your own projects. The book also focuses on teaching core Java programming concepts and applying them to game development.